Pemetaan Tren Penelitian dan Identifikasi Kesenjangan Ilmiah dalam Energi Air (Hydropower): Studi Bibliometrik - RafaAdhityaDharmawwangsa Nasution; M Ridho Rahman Hasibuan; Hasyim Fadillah Lubis; Erza Arkan Zharif; Muhammad Ashbar As-Silmy (LPPMP Universitas Bhayangkara Jakarta Raya, 2026)
This study discusses the utilization of hydropower through micro-hydropower plants as a sustainable renewable energy solution, particularly in rural areas. The objective of this research is to analyze water resource potential, design the power generation system, and evaluate the performance and efficiency of the developed micro-hydropower system. The methods employed include field surveys, measurement of water discharge and head, as well as calculations of theoretical and actual power based on hydraulic and mechanical parameters.The results indicate that the water energy potential at the study site is significant and feasible for development as an alternative electricity source. The designed system is capable of producing stable electrical power, with efficiency influenced by flow conditions, turbine type, and installation quality. Furthermore, the implementation of micro-hydropower plants has been shown to improve electricity access for local communities and support sustainable development in remote areas.In conclusion, micro-hydropower plants have strong potential as an environmentally friendly energy solution with relatively low operational costs, although further optimization in design and management is required to enhance system efficiency and sustainability.